The Partitioning of Small Aromatic Molecules to Air-Water and Phospholipid Interfaces Mediated by Non-Hydrophobic Interactions - Perkins, Russell J; Kukharchuk, Alexandra; Delcroix, Pauline; Shoemaker, Richard K; Roeselová, Martina; Cwiklik, Lukasz; Vaida, Veronica (The journal of physical chemistry. B, 2016)
Phenylalanine has an important role both in normal biological function and in disease states such as phenylketonuria (PKU) and amyloid fibril diseases. Two crucial aspects of phenylalanine behavior in biological systems are its preferential partitioning into membranes and its propensity to cluster. In order to examine the intermolecular interactions that give rise to this behavior, the surface partitioning behavior was investigated for a series of molecules structurally related to phenylalanine (phenylglycine, phenylacetic acid, and tyrosine) both experimentally and by molecular dynamics simulations. Surface tension measurements were performed over time for aromatic solutions both in the presence and in the absence of 1,2-dipalmitoyl-sn-glycero-3-phosphatidylcholine (DPPC) monolayer films, which functioned as simple model membranes. The observed trends in surface activity defy simple predictions based on solubility and hydrophobicity. The possibility of clustering is investigated through a combination of Langmuir trough, nuclear magnetic resonance (NMR), fluorescence self-quenching, and mass spectroscopy measurements. It is concluded that clustering does not occur in solution to a significant extent for these molecules, but interfacial clustering is likely. An explanation for observed trends in surface activity is presented on the basis of cluster stability and molecular conformational flexibility.
Keywords: Unilamellar Liposomes; unilamelární lipozómy; Spectrometry, Fluorescence; povrchové vlastnosti; Tyrosine; 1,2-dipalmitoylfosfatidylcholin; fluorescenční spektrometrie; rozpustnost; Cluster Analysis; vzduch; magnetická rezonanční spektroskopie; Air; simulace molekulární dynamiky; Molecular Dynamics Simulation; 1,2-Dipalmitoylphosphatidylcholine; voda; Phenylalanine; Solubility; shluková analýza; Water; fenylalanin; Magnetic Resonance Spectroscopy; hmotnostní spektrometrie; tyrosin; Surface Properties; Mass Spectrometry